Evaluation of a cooled wheel cleaning jet in minimum quantity lubrication grinding process - Javaroni, Rafael Liberatti [UNESP] (2020)
The application of the minimum quantity lubrication (MQL) technique in grinding processes is still limited due to the frequent occurrence of overheating and wheel clogging. In this context, this research evaluates a cooled wheel cleaning jet (CWCJ) under different temperatures, applied simultaneously to MQL in the cylindrical grinding of AISI 4340 quenched and tempered steel, using a CBN wheel. For comparison, tests with the MQL, MQL + WCJ, and conventional techniques were also performed. Surface roughness, microhardness, and roundness deviation of the workpieces, wheel wear, and grinding power were the assessed output parameters. The machined workpieces were evaluated by optical, confocal, and scanning electron microscopies. The MQL + WCJ outperformed MQL and MQL + WCJ in all the tested conditions. The application of the cooled wheel cleaning jet reduced by up to 79% the surface roughness, 82% the wheel wear, 76% the roundness deviation, and 37% the grinding power, regarding MQL and MQL + WCJ techniques, contributing towards a sustainable and high-quality grinding process.